Pathologic and molecular subtypes characteristics of our breast cancer patients in Kosovo - B Profka Haxhiu; G Kondov; L Abdullahu; F Kurshumliu; B Kondov (Macedonian Association of Anatomists and Morphologists, 2025)
Aim: Тo classify breast cancer cases by molecular subtypes (luminal A, luminal B (HER2 positive), luminal B (HER2 negative), HER2 positive, triple negative). Secondly, to analyze the associations between the immunohistochemical markers, molecular subtype and known prognostic factors (stage, grade, age, location). Material and methods: In this study patients are enrolled prospectively from the oncology clinic 100 patients. All of them are breast cancer patients who have undergone different methods of treatment. Results: Radical mastectomy (RM) remains the cornerstone of surgery compared to breast conserving surgery (BCS) as we see from our result where 83% undergone to radical mastectomy and 16% BCS. All molecular subtypes have the primary treatment radical mastectomy plus lymph node dissection. Even in Luminal A subtype the ratio between BCS and RM is 1:3 Conclusion: Molecular subtypes correlate with tumor volume and disease stage, indicating differences in disease progression. Given that a significant portion of cases were diagnosed at locally advanced stages during initial presentation, mastectomy remained the preferred choice over breast-conserving surgery. This preference may be attributed to the need for more aggressive treatment approaches to address the advanced disease stage in the time of diagnosis.
Keywords: breast cancer; molecular subtypes